A comparative study evaluating the effectiveness of nursing assessment formats. - O'Connell, Beverly O. (Curtin University, 1992)
Nursing assessment is the foundation of the nursing process. The focus and type of data collected, during such assessment is central to the effectiveness of the diagnostic process and subsequent planned nursing interventions. Whilst there is a multiplicity of factors that impact upon the diagnostic process, eminent nurse theorists espouse a relationship between assessment formats and diagnostic accuracy. This study evaluates the effectiveness of two types of assessment formats by addressing the following questions. When student and registered nurses use a Gordons Functional Health Pattern (GFHP) assessment format compared to using a Review of Biological Systems (ROBS) assessment format is there a difference in: (1) the number and type of diagnoses identified? and (2) the number of criteria achieved within the Standards for Nursing Care (ANF, 1989)?A developed case study with verified diagnoses was used. Professional actors played the part of the client and followed a standard script. Volunteer student and registered nurses (N=100) were randomly assigned to the two types of assessment formats. They were required to conduct an assessment of the client and state the nursing diagnoses. Data were analysed using Multivariate Analysis of Variance.Results indicated that when both groups of nurses used the GFHP format they stated significantly more correct and more diverse categories of diagnoses and significantly fewer diagnoses which were classified as being incorrect and medical, than when they used the ROBS format. In addition, when student and registered nurses used the GFHP format, they elicited significantly more information that complied with the criteria outlined within the Standards for Nursing Care (ANF, 1989), than when they used the ROBS format.The findings of this study indicate that both student and registered nurses are guided by the cues on the assessment format. Therefore, the choice and design of nursing assessment forms are critical as they affect diagnostic accuracy.